A Study of the Quantitative Analysis of Parts of Speech in the Educational Book of Mongolian Language: (Primary School Grades I-V) - Tuvdendorj, Batbyamba (Mongolian Language and Literature Studies, 2025)
We created electronic database by collecting Mongolian language textbooks for elementary school which were published within the framework of the Mongolian language program implemented in the field of education in Mongolia. Then based on it, the total number of words, syllables and letters of the textbook was recorded using language processing programs that were combined with the manual marking method. We aimed to present the results of the research, which was classified by parts of speech and the frequency with this article. For the accomplishment of this objective, we compared and processed textbooks for grades 1-5, and explained the results of data-based research that can be used as a guide for specialized researchers. Our purpose is clarifying the importance of studying the language of Mongolian textbook for elementary school which provide mother tongue education with a scientific basis from the aspect of computation. Монгол хэлний сурах бичгийн цахим санд суурилсан үгийн аймгийн бүртгэл судалгаа (Ерөнхий боловсролын сургуулийн I-V анги) Хураангуй: Монгол улсын боловсролын салбарт мөрдөгдөж байгаа монгол хэлний хөтөлбөрийн хүрээнд бага ангийн монгол хэлний сурах бичгүүдийг цуглуулан цахим сан бүрдүүлэх ажлыг гүйцэтгэж, түүндээ тулгуурлан хэл боловсруулалтын программуудыг гараар тэмдэглэгээ хийх аргатай хослуулан, сурах бичгийн нийт үгийг үгийн аймгаар ангилж, давтамжийг тооцоолсон судалгааны үр дүнгээ энэхүү өгүүллээр танилцуулахыг зорив. Бид энэхүү зорилтынхоо хүрээнд 1-5-р ангийн монгол хэлний сурах бичгүүдийг харьцуулан үзэж, боловсруулалт хийж, тусгай мэргэжлийн судлаачдад гарын авлага болгон ашиглах боломжтой тоо баримтад суурилсан судалгааны үр дүнг тайлбарлан өгүүллээ. Энэ нь эх хэлний боловсролыг олгодог бага ангийн монгол хэлний сурах бичгийн хэлийг тооцооллын үүднээс шинжлэх ухааны үндэслэлтэйгээр судлахын ач холбогдлыг тодруулахад чиглэсэн билээ. Түлхүүр үгс: сурах бичиг, цахим сан, өгөгдөл, үгийн аймаг, давтамж